Penyuluhan Bahaya Gangguan Kecemasan pada Masyarakat Pesisir Baubau - Nurul Ahwat Rantekata; Nurdin Nurdin; Asman Asman; Ilham La jamri (Pusat Riset dan Inovasi Nasional, 2021)
This community service and research aims to increase public understanding of mental health, especially anxiety disorders. The material provided by the lecturers of the Islamic Counseling Guidance study program at STAI YPIQ Baubau is very useful for providing enlightenment on what the community has felt so far, who previously may not have understood their physical and mental condition. The activities carried out for two days which took place in the hall of the village office had a very positive impact on the community. The community was very happy with the counseling, education and training because programs like this are rarely held due to the lack of counseling practitioners in the Pesisir Baubau area. The target of this program is given to the entire community, both parents, adults and children. Seven students from the Islamic Counseling Guidance Study Program also participated in this activity. In addition to being able to help the smooth running of this activity, they also gained a lot of knowledge from the activities carried out.